Aromatization of Stobbe Reaction Products - Jabbar, Saba; Banerjee, Shubhra (Asian Journal of Chemistry, 2010)
Stobbe condensation products (diacids) of dimethylsuccinate and dimethyl itaconate with cyclohexanone aromatize into aromatic lactones when N-bromosuccinimide (NBS) in CCl4 with benzoylperoxide is used but give back the original acids when sulphur in xylene is the reagent for aromatization.